Is Innovation Relevant to Drive Marketing Strategies in Improving the Performance of Business Actors in Shopee E-Commerce? - Triapnita Nainggolan, Nana; Ekana Nainggolan, Lora; Lie, Darwin (Publisher Cv. Inara, 2025)
E-commerce is an extraordinary example of an online market product that is a breakthrough for people in buying and selling activities, with a wider reach. Digital enables transactions and processes within a company, involving information systems under the control of the company. The role of social media also contributes to encouraging consumers to shop in E-commerce. Various promos and advertisements as a form of marketing strategy offered have an impact on people's interest in online shopping. With these various promos and advertisements, there is a contest to attract buyers. However, the level of public satisfaction with marketing on Shopee is not optimal, where the level of consumer trust in business owners is still low. This research aims to explain the relationship and influence of innovation in driving marketing strategies to improve the performance of business actors on Shopee. This study uses a quantitative descriptive technique with an exploratory survey approach for this study. The data used was sourced from offline surveys. The sample of this study is all Shopee Pematang Siantar E-commerce users who are classified as millennials totaling 99 people. This non-probability purposive sampling technique was chosen because there are no statistics that determine the size of the population. The data analysis technique used is the Partial Least Square Structural Equation Model used. Hypothesis testing was carried out with the results of innovation affecting marketing strategies, the second hypothesis was marketing strategies affecting the performance of business actors, The original sample value was positive which showed that the direction of the relationship between marketing strategies and the performance of business actors was positive, so it could be concluded that the second hypothesis was accepted. The marketing strategies implemented by Shopee in improving the company's performance are still not optimal. It is recommended that the selection of suppliers in providing products on Shopee is more selective so that the quality of the product, product variety and content in the application are in accordance with what is displayed. For the provision of discounts in the product distribution process to consumers so that it is clearly informed to each consumer account so that there is no misperception. Innovation needs to be improved by Shopee in terms of other payment services such as payments for the use of transportation services. So that consumers who have the SPayLater application can make their payments more conveniently. Shopee's performance still needs to be improved through the addition of suppliers from outside Indonesia so that consumers in Indonesia who want products from abroad can make purchases on the Shopee application so that the number of consumer purchases will increase.